Lithium supplement and preparation method thereof, positive electrode slurry and battery
By using lithium supplement agent with the core chemical formula of LixM1yM21-yO6 on the positive electrode side of the lithium battery, and forming a cladding layer containing lithium metal oxide and carbon material on its surface, the high decomposition potential of lithium supplement agent in the prior art is solved. The problem of low lithium ion migration rate has achieved higher lithium supplement capacity and improved energy density and cycle life of lithium batteries.
Patent Information
- Application Number
- CN202410382941.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The existing positive electrode side lithium supplement technology has many problems in actual production and application, especially the high decomposition potential of lithium supplement agents and the low migration rate of lithium ions, which leads to a decrease in the energy density of lithium batteries and a shortened cycle life.
Lithium supplementation agent with the kernel chemical formula of LixM1yM21-yO6 is used, where 6≤x≤8, 0
The lithium supplement capacity and lithium ion migration rate of lithium supplement agents are improved, the decomposition potential is reduced, the processing performance is improved, and the energy density and cycle life of lithium batteries are enhanced.
Smart Images

Figure CN118299685B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of batteries, and specifically, to a lithium supplement agent, a preparation method thereof, a positive electrode slurry, and a battery. Background Art
[0002] During the first charging process of a lithium-ion battery, a solid electrolyte interface film (SEI) is formed at the negative electrode interface, resulting in irreversible loss of the battery's capacity, and further causing a decrease in the energy density of the lithium-ion battery. The capacity loss during the formation of the SEI film can be effectively alleviated through lithium supplement technology. There are mainly two ways of lithium supplement technology: lithium supplement on the positive electrode side and lithium supplement on the negative electrode side. Among them, the lithium supplement technology on the negative electrode side requires the use of metallic lithium materials, which has problems such as complex processes and high environmental requirements. The lithium supplement technology on the positive electrode side has higher safety and compatibility, and higher feasibility. However, there are still many problems in the actual production and application of the lithium supplement technology on the positive electrode side, which need to be further solved. Summary of the Invention
[0003] In the first aspect of the present application, a lithium supplement agent is proposed, including: a core, the core satisfies the chemical formula Li x M1 y M2 1-y O6, where 6≤x≤8, 0<y<1, M1 is at least one of Zr, Nb, Sb, Bi, Ru, Ta, Sn, Hf, Ir, Pr, Pt, Np; M2 is at least one of W, Ge, Ca, Ce, K, Ta; a coating layer, the coating layer is at least located on a part of the surface of the core, and the coating layer includes a lithium-containing metal oxide and a carbon material, where the lithium-containing metal oxide satisfies the chemical formula Li a M b O c , where 1.8≤a≤2, 0.7≤b≤1.1, 2.8≤c≤3, M includes Ti and / or Zr. Among them, the peak intensity of the X-ray diffraction peak of the lithium supplement agent at a 2θ diffraction angle of 20.1° - 20.3° is S1, and the peak intensity of the X-ray diffraction peak of the lithium supplement agent at a 2θ diffraction angle of 17° - 17.3° is S2, and S1 / S2 is 0.02 - 0.05. Thus, the lithium supplement agent has a high lithium supplement capacity, a high lithium ion migration rate, and excellent processing performance.
[0004] In some embodiments, the mass fraction of the lithium-containing metal oxide in the lithium supplement agent is 0.01% - 0.1%, and / or the mass fraction of the carbon material in the lithium supplement agent is 0.01% - 0.5%. Thus, the lithium supplement agent has a high lithium supplement capacity.
[0005] In some embodiments, the unit cell parameters of the core satisfy a=b, a≠c, wherein c / a is 2-3. Thus, the lithium ion migration rate of the lithium supplement can be increased.
[0006] In some embodiments, a is 0.4 nm to 0.7 nm, and c is 1.4 nm to 1.6 nm. Thus, the lithium ion migration rate of the lithium supplement can be further improved.
[0007] In some embodiments, the Dv50 particle size of the core is 1 μm-10 μm, and / or the thickness of the coating layer is 50 nm-500 nm. Thus, the coating layer can improve the storage performance of the lithium supplement agent, enhance the conductivity of the lithium supplement agent, and help the lithium supplement agent to fully exert its lithium supplement capacity.
[0008] In some embodiments, the core comprises Li8Zr 0.9 W 0.1 O6、Li7Nb 0.8 Ta 0.2 O6、Li7Sb 0.9 Ta 0.1 O6、Li7Ru 0.7 W 0.2 Ce 0.1 O6、Li8Sn 0.9 Ca 0.1 O6、Li8Hf 0.7 W 0.2 Ca 0.1 O6、Li8Ir 0.6 W 0.2 Ce 0.2 O6、Li8Pr 0.5 W 0.3 Ca 0.2 O6、Li8Pt 0.7 W 0.2 Ca 0.1 At least one of O6. Thus, the lithium replenishing capacity of the lithium replenishing agent can be effectively increased and the decomposition potential of the lithium replenishing agent can be reduced.
[0009] In some embodiments, the graphitization degree of the carbon material is greater than or equal to 60%. Thus, the conductivity of the lithium supplement can be further improved.
[0010] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned lithium supplement, comprising: subjecting a lithium source, an M1 source, and an M2 source to a first sintering treatment in an oxygen-containing atmosphere to obtain an inner core; subjecting the inner core, an M source, and a carbon source to a second sintering treatment in an inactive atmosphere to form a coating layer on at least a portion of the surface of the inner core to obtain the lithium supplement. Thus, the aforementioned lithium supplement with better lithium supplement performance can be obtained by a simple method.
[0011] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium oxide; and / or the M1 source includes at least one of M1 oxide, M1 chloride, M1 nitrate, and M1 hydroxide; and / or the M2 source includes at least one of M2 oxide, M2 chloride, M2 nitrate, and M2 hydroxide. This helps to form a core with a higher lithium supplement capacity.
[0012] In some embodiments, the temperature of the first sintering treatment is 700° C.-1200° C., and the time of the first sintering treatment is 8 h-24 h. This helps to obtain pure phase core particles with a moderate particle size.
[0013] In some embodiments, the M source includes at least one of zirconium propoxide, zirconium oxide, zirconium nitrate, zirconium oxychloride, lithium zirconate, zirconium chloride, titanium oxide, titanium tetrachloride, titanium nitrate, and titanium alkoxide; and / or the carbon source includes at least one of glucose, starch, sucrose, and graphite. Thus, it is helpful to form a lithium-containing metal oxide on the surface of the core.
[0014] In some embodiments, the temperature of the second sintering treatment is 400° C.-800° C., and the time of the second sintering treatment is 6 h-10 h. This helps to form lithium-containing metal oxides and carbon materials in the coating layer.
[0015] In some embodiments, the method further includes: before the second sintering process, mixing the core, the M source, and the carbon source in a solvent and performing a drying process, thereby helping to improve the coating uniformity of the coating layer.
[0016] In some embodiments, the solvent includes at least one of ethanol and isopropanol; and / or the drying process includes at least one of spray drying, freeze drying, and flash drying. This helps to improve the coating uniformity of the coating layer.
[0017] In the third aspect of the present application, the present application proposes a positive electrode slurry, including the aforementioned lithium supplement agent, or the lithium supplement agent prepared by the aforementioned method. Therefore, the positive electrode slurry has all the characteristics and advantages of the aforementioned lithium supplement agent and the method for preparing the lithium supplement agent, which will not be repeated here.
[0018] In some embodiments, the viscosity of the positive electrode slurry is 1000 mPa·s-8000 mPa·s, which is beneficial to improve the processing performance of the positive electrode slurry.
[0019] In the fourth aspect of the present application, the present application proposes a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer at least located on one side of the positive electrode current collector, wherein the positive electrode active material layer is prepared by using the above-mentioned positive electrode slurry. Therefore, the battery has all the characteristics and advantages of the above-mentioned positive electrode slurry, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 This is a scanning electron microscope image of the lithium supplement agent of Example 1 of the present application;
[0022] Figure 2 X-ray diffraction patterns of the lithium supplement agents of Example 1 and Comparative Example 5 of the present application;
[0023] Figure 3 This is a charge and discharge curve diagram of a battery made with the lithium supplement agent of Example 1 of the present application. DETAILED DESCRIPTION
[0024] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0025] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0026] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.
[0027] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.
[0028] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0030] The positive electrode side lithium supplement in the related art includes binary lithium-containing compounds, such as Li2O, Li2O2, Li3N, and ternary lithium-containing compounds, such as Li2NiO2, Li6CoO4, Li5FeO4, etc. Binary lithium-containing compounds have poor stability in the atmospheric environment and are difficult to be applied in industrial applications. Ternary lithium-containing compounds are more stable than binary lithium-containing compounds, but ternary lithium-containing compounds also have the disadvantages of strong surface alkalinity and high decomposition potential. Specifically, when the lithium supplement is added to the positive electrode slurry, the strong alkaline surface of the lithium supplement will cause the occurrence of lithium precipitation reaction, which will then increase the alkalinity of the positive electrode slurry, causing the viscosity of the positive electrode slurry to increase significantly or even form a jelly-like slurry, which cannot meet the coating requirements; when the decomposition potential of the lithium supplement is too high, a higher voltage needs to be applied during the first charging process of the battery to fully release the lithium supplement capacity in the lithium supplement. When the voltage applied during the first charging process is too high, the positive electrode active material in the positive electrode active material layer will undergo irreversible structural changes, resulting in a decrease in the lithium deintercalation sites of the positive electrode active material and a decrease in the energy density of the battery; when the voltage applied during the first charging process is too low, the lithium replenishing capacity of the lithium replenisher cannot be fully utilized and the lithium replenishing effect of the lithium replenisher is poor.
[0031] In the present application, by optimizing the element composition of the lithium supplement core, on the basis of the ternary lithium-containing lithium supplement, the lithium ion migration rate of the lithium supplement core is further improved by adding doping elements. Specifically, the lithium supplement core satisfies the chemical formula Li x M1 y M2 1-yO6, where 6 ≤ x ≤ 8 and 0 < y < 1. Among them, the ternary lithium-containing compound containing element M1 has a relatively high theoretical capacity, which can effectively improve the lithium supplement capacity of the lithium supplement agent. Element M2 can provide a relatively small lithium supplement capacity compared with element M1, but it has a larger ionic radius than element M1. After doping with element M2, the interlayer spacing between the inner core and the layered structure can be increased, which is helpful for the rapid insertion and extraction of lithium ions. Therefore, the inner core of the lithium supplement agent has a high lithium supplement agent capacity, a high lithium supplement capacity, and a high lithium ion migration rate. Further, since the alkaline surface of the aforementioned inner core of the lithium supplement agent may cause problems such as gelation of the positive electrode slurry, a coating layer is formed on the surface of the aforementioned inner core of the lithium supplement agent. The coating layer includes a lithium-containing metal oxide and a carbon material. Among them, the lithium-containing metal oxide in the coating layer can effectively inhibit the reaction of the inner core with moisture, carbon dioxide, etc. in the air to generate impurities such as lithium hydroxide or lithium carbonate. However, the conductivity of the lithium-containing metal oxide is poor. By adding an appropriate amount of carbon material to the coating layer, the conductivity of the coating layer can be effectively improved, thereby improving the surface electron conductivity of the lithium supplement agent and improving the lithium ion and electron transport channels of the lithium supplement agent.
[0032] When the lithium supplement agent has a characteristic diffraction peak for X-rays within the 2θ diffraction angle range of 20.1° - 20.3°, it indicates that the lithium-containing metal oxide in the coating layer is in a tetragonal phase structure (110 crystal plane). When the lithium supplement agent has a characteristic diffraction peak for X-rays within the 2θ diffraction angle range of 17° - 17.3°, it indicates that the inner core of the lithium supplement agent is in a hexagonal phase structure (101 crystal plane). Further, when the peak intensity of the diffraction peak of the lithium supplement agent for X-rays within the 2θ diffraction angle range of 20.1° - 20.3° is S1, and the peak intensity of the diffraction peak of the lithium supplement agent for X-rays within the 2θ diffraction angle range of 17° - 17.3° is S2, and S1 / S2 is 0.02 - 0.05, the phase ratio between the hexagonal phase structure inner core of the lithium supplement agent and the tetragonal phase structure coating layer is relatively appropriate. At this time, the hexagonal phase structure inner core has a high lithium ion migration rate, which is beneficial to the full extraction of lithium ions in the inner core; the lithium-containing metal oxide with a tetragonal phase structure not only has high structural stability, can effectively inhibit the reaction of the inner core with moisture, carbon dioxide, etc. to generate impurities, but also has good lithium insertion and extraction characteristics, so that the surface coating layer jointly formed by the lithium-containing metal oxide and the carbon material has a small influence on the lithium supplement performance of the inner core, effectively improving the lithium ion and electron transport channels of the lithium supplement agent.
[0033] In the first aspect of the present application, the present application proposes a lithium supplement agent, including: an inner core, and the inner core satisfies the chemical formula Li x M1 y M2 1-yO6, where 6 ≤ x ≤ 8, 0 < y < 1, M1 is at least one of Zr, Nb, Sb, Bi, Ru, Ta, Sn, Hf, Ir, Pr, Pt, Np; a coating layer, the coating layer is at least located on a part of the surface of the core, the coating layer includes a lithium-containing metal oxide and a carbon material, where the lithium-containing metal oxide satisfies the chemical formula Li a M b O c , where 1.8 ≤ a ≤ 2, 0.7 ≤ b ≤ 1.1, 2.8 ≤ c ≤ 3, M includes Ti and / or Zr. Wherein, the peak intensity of the X-ray diffraction peak of the lithium supplement agent at a 2θ diffraction angle of 20.1° - 20.3° is S1, and the peak intensity of the X-ray diffraction peak of the lithium supplement agent at a 2θ diffraction angle of 17° - 17.3° is S2, and S1 / S2 is 0.02 - 0.05. Thus, the aforementioned lithium supplement agent has a high lithium supplement capacity and a high lithium ion migration rate. Among them, there is a stable tetragonal phase coating layer on the surface of the hexagonal phase core. When the ratio of S1 to S2 meets the aforementioned limit, the coating layer can effectively improve the stability of the core and reduce the increase in the viscosity of the positive electrode slurry caused by the alkalinity on the surface of the core during the use of the lithium supplement agent, and the processing performance is relatively good. When the aforementioned lithium supplement agent is applied to the lithium supplement technology on the positive electrode side, during the charging process of the battery, the lithium supplement agent can be fully decomposed and release active lithium ions to supplement the loss of active lithium caused by the formation of the SEI film, achieving the effect of improving the energy density and cycle life of the lithium battery.
[0034] As an example, x can be 6, 6.5, 7, 7.5 or 8.
[0035] As an example, y can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9.
[0036] As an example, a can be 1.8, 1.9 or 2.
[0037] As an example, b can be 0.7, 0.8, 0.9, 1 or 1.1.
[0038] As an example, c can be 2.8, 2.9 or 3.
[0039] As an example, S1 / S2 can be 0.02, 0.03, 0.04 or 0.05.
[0040] The "diffraction peak intensity ratio" in this application has a well-known meaning in the art and can be measured by instruments and methods well-known in the art. For example, it can be obtained by the following method: using an X-ray automatic diffractometer to perform phase and crystal structure analysis, with an operating voltage of 40 kV, an operating current of 250 mA, continuous scanning, a scanning speed of 4° / min, a step size of 0.02°, and a scanning angle range of 10°-80°.
[0041] In some embodiments, the mass fraction of the lithium-containing metal oxide in the lithium supplement agent is 0.01%-0.1%, and / or the mass fraction of the carbon material in the lithium supplement agent is 0.01%-0.5%.
[0042] As an example, the mass fraction of the lithium-containing metal oxide in the lithium supplement may be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%.
[0043] When the mass fraction of the lithium-containing metal oxide in the lithium supplement is within the above range, the lithium-containing metal oxide in the coating layer can take advantage of its ultra-high ion conductivity and inhibit the reaction of the core with moisture, carbon dioxide, etc., and prevent the formation of an impurity layer on the surface of the core.
[0044] As an example, the mass fraction of the carbon material in the lithium supplement may be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.
[0045] When the mass fraction of the carbon material in the lithium supplement agent is within the above range, the carbon material in the coating layer can effectively improve the conductivity of the coating layer, thereby improving the surface electronic conductivity of the lithium supplement agent, improving the transmission channels of lithium ions and electrons of the lithium supplement agent, and has little effect on the lithium supplement capacity of the lithium supplement agent.
[0046] In some embodiments, the unit cell parameters of the core satisfy a=b, a≠c, wherein c / a is 2-3. Thus, the lithium ion migration rate of the lithium supplement can be increased.
[0047] As examples, c / a may be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9 or 3.
[0048] When the unit cell parameters of the inner core satisfy a=b, a≠c, the inner core is a hexagonal crystal system. The characteristic symmetry of the hexagonal crystal system determines that the basis vector characteristics corresponding to the unit cell of the hexagonal crystal system are that the two minor axes are perpendicular to the main axis, the two minor axis basis vectors are equal in size, and the angle between the minor axes is 120°, that is, its unit cell parameters are a=b≠c, α=β=90°, γ=120°. At this time, the unit cell is a layered structure, and then by matching elements with different chemical valence states and designing unbalanced charges in the transition metal layer, it is helpful to form lithium ion layer vacancies and realize rapid transmission and efficient utilization of lithium ions.
[0049] In some embodiments, a is 0.4 nm to 0.7 nm, and c is 1.4 nm to 1.6 nm. Thus, the lithium ion migration rate of the lithium supplement can be further improved.
[0050] As an example, a may be 0.4 nm, 0.45 nm, 0.5 nm, 0.55 nm, 0.6 nm, 0.65 nm, or 0.7 nm.
[0051] As an example, c may be 1.4 nm, 1.45 nm, 1.5 nm, 1.55 nm, or 1.6 nm.
[0052] The "lattice parameter" in this application has a well-known meaning in the art and can be measured using instruments and methods well-known in the art. For example, the lattice parameter can be obtained by X-ray diffraction testing.
[0053] In some embodiments, the Dv50 particle size of the core is 1 μm-10 μm, and / or the thickness of the coating layer is 50 nm-500 nm. Thus, the coating layer can improve the storage performance of the lithium supplement agent, enhance the conductivity of the lithium supplement agent, and help the lithium supplement agent to fully exert its lithium supplement capacity.
[0054] As an example, the Dv50 particle size of the core can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 10μm.
[0055] As an example, the thickness of the coating layer may be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm or 500 nm.
[0056] In some embodiments, the core comprises Li8Zr 0.9 W 0.1 O6、Li7Nb 0.8 Ta 0.2 O6、Li7Sb 0.9 Ta0.1 O6、Li7Ru 0.7 W 0.2 Ce 0.1 O6、Li8Sn 0.9 Ca 0.1 O6、Li8Hf 0.7 W 0.2 Ca 0.1 O6、Li8Ir 0.6 W 0.2 Ce 0.2 O6、Li8Pr 0.5 W 0.3 Ca 0.2 O6、Li8Pt 0.7 W 0.2 Ca 0.1 At least one of O6. Thus, the lithium replenishing capacity of the lithium replenishing agent can be effectively increased and the decomposition potential of the lithium replenishing agent can be reduced.
[0057] When the inner core of the lithium supplement agent includes the aforementioned substances, the inner core has a higher lithium supplement capacity and a higher lithium supplement agent capacity.
[0058] As an example, Li8Zr 0.9 W 0.1 The theoretical capacity of O6 is 883 mAh / g, Li7Nb 0.8 Ta 0.2 The theoretical capacity of O6 is 790mAh / g, Li7Sb 0.9 Ta 0.1 The theoretical capacity of O6 is 704mAh / g, Li7Ru 0.7 W 0.2 Ce 0.1 The theoretical capacity of O6 is 764mAh / g, Li8Sn 0.9 Ca 0.1 The theoretical capacity of O6 is 793mAh / g, Li8Hf 0.7 W 0.2 Ca 0.1 The theoretical capacity of O6 is 650mAh / g, Li8Ir 0.6 W 0.2 Ce 0.2 The theoretical capacity of O6 is 624mAh / g, Li8Pr 0.5 W 0.3 Ca 0.2 The theoretical capacity of O6 is 733mAh / g, Li8Pt 0.7 W 0.2 Ca 0.1 The theoretical capacity of O6 is 619 mAh / g.
[0059] In some embodiments, the graphitization degree of the carbon material is greater than or equal to 60%. Thus, the conductivity of the lithium supplement can be further improved.
[0060] When the graphitization degree of the carbon material is within the aforementioned range, the closer the internal structure of the carbon material is to ideal graphite, the better the conductive property is.
[0061] In the second aspect of the present application, the present application proposes a method for preparing the aforementioned lithium supplement, thereby, the aforementioned lithium supplement with better lithium supplement performance can be prepared by a simple method. Specifically, the method for preparing the lithium supplement may include:
[0062] S100: The lithium source, M1 source, and M2 source are subjected to a first sintering treatment in an oxygen-containing atmosphere.
[0063] In some embodiments, in this step, the M1, M2 sources and the lithium source are mixed uniformly according to the amount ratio of the substance in the chemical formula, and sintered in an oxygen-containing atmosphere to obtain a lithium ion battery having a chemical formula of Li x M1 y M2 1-y O6 lithium supplement core, where 6≤x≤8, 0 <y<1。
[0064] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, and lithium oxide.
[0065] In some embodiments, the M1 source includes at least one of an oxide of M1, a chloride of M1, a nitrate of M1, and a hydroxide of M1.
[0066] In some embodiments, the M2 source includes at least one of an oxide of M2, a chloride of M2, a nitrate of M2, and a hydroxide of M2.
[0067] In some embodiments, the temperature of the first sintering treatment is 700° C.-1200° C., and the time of the first sintering treatment is 8 h-24 h. This helps to obtain pure phase core particles with a moderate particle size.
[0068] As an example, the temperature of the first sintering process may be 700°C, 800°C, 900°C, 1000°C, 1100°C, or 1200°C.
[0069] As an example, the time of the first sintering process may be 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h or 24 h.
[0070] When the temperature and time of the first sintering treatment are within the aforementioned range, it is conducive to the formation of a hexagonal phase structure core, and the physical phase structure is more stable, with less impurities, and the particle size of the formed core particles is moderate.
[0071] In some embodiments, the oxygen-containing atmosphere may be an oxygen-containing atmosphere such as oxygen or air.
[0072] S200: subjecting the core, M source and carbon source to a second sintering process in an inactive atmosphere.
[0073] In some embodiments, in this step, the M source is uniformly mixed with the core, and then mixed with the carbon source, and then sintered in an inactive atmosphere to form a coating layer on at least a portion of the surface of the core to obtain the lithium supplement.
[0074] In some embodiments, the M source includes at least one of zirconium propoxide, zirconium oxide, zirconium nitrate, zirconium oxychloride, lithium zirconate, zirconium chloride, titanium oxide, titanium tetrachloride, titanium nitrate, and titanium alkoxide.
[0075] In some embodiments, the carbon source includes at least one of glucose, starch, sucrose, and graphite. This helps to form a lithium-containing metal oxide on the surface of the inner core.
[0076] In some embodiments, the temperature of the second sintering treatment is 400° C.-800° C., and the time of the second sintering treatment is 6 h-10 h. This helps to form lithium-containing metal oxides and carbon materials in the coating layer.
[0077] As an example, the temperature of the second sintering process may be 400°C, 500°C, 600°C, 700°C, or 800°C.
[0078] As an example, the time of the second sintering process may be 6 h, 7 h, 8 h, 9 h or 10 h.
[0079] When the temperature and time of the second sintering treatment are within the aforementioned range, it is helpful to form a tetragonal lithium-containing metal oxide and a carbon material with a high degree of graphitization, and the physical phase structure is more stable and carbon loss is less.
[0080] In some embodiments, an inactive atmosphere is required during the second sintering process to form the coating layer, thereby effectively reducing the reaction between the carbon source and the active atmosphere, thereby alleviating carbon loss. For example, the carbon source will be oxidized in an active atmosphere, such as an oxygen-containing atmosphere, to generate carbon dioxide or carbon monoxide gas, which will then escape and cause carbon loss.
[0081] As an example, the inactive atmosphere may include a non-oxygen-containing, non-hydrogen-containing atmosphere such as nitrogen or argon.
[0082] In some embodiments, the method further includes: before the second sintering process, the core, the M source, and the carbon source are mixed in a solvent and dried. Thus, the core, the carbon source, and the M source can be fully dispersed in the solvent, which helps to mix the core, the M source, and the carbon source more evenly. The solvent is then removed by drying, which helps to improve the coating uniformity of the coating layer.
[0083] In some embodiments, the solvent includes at least one of ethanol and isopropanol.
[0084] In some embodiments, the drying process comprises at least one of spray drying, freeze drying, and flash drying.
[0085] In the third aspect of the present application, the present application proposes a positive electrode slurry, including the aforementioned lithium supplement agent, or the lithium supplement agent prepared by the aforementioned method. Therefore, the positive electrode slurry has all the characteristics and advantages of the aforementioned lithium supplement agent and the method for preparing the lithium supplement agent, which will not be repeated here.
[0086] In some embodiments, the viscosity of the positive electrode slurry is 1000 mPa·s-8000 mPa·s, which is beneficial to improve the processing performance of the positive electrode slurry.
[0087] By forming a coating layer on the surface of the lithium supplement agent core, the influence of the alkaline surface of the core on the stability of the slurry is effectively suppressed. When the lithium supplement agent is added to the positive electrode slurry, the strong alkaline surface of the lithium supplement agent will not cause lithium precipitation reaction, thereby effectively alleviating the significant increase in the viscosity of the positive electrode slurry caused by the increase in the alkalinity of the positive electrode slurry, which helps the positive electrode slurry meet the coating requirements.
[0088] As an example, the positive electrode material, the lithium supplement, the solvent (such as N-methylpyrrolidone), the binder (such as polyvinylidene fluoride), and the conductive agent (such as carbon black, acetylene black) can be mixed in a mass ratio of 90:2:100:4:4 to obtain the positive electrode slurry.
[0089] In the fourth aspect of the present application, the present application proposes a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer at least located on one side of the positive electrode current collector, wherein the positive electrode active material layer is prepared by using the above-mentioned positive electrode slurry. Therefore, the battery has all the characteristics and advantages of the above-mentioned positive electrode slurry, which will not be described in detail here.
[0090] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.
[0091] Example 1
[0092] (1) Lithium carbonate (lithium source), zirconium dioxide (M1 source), and tungsten oxide (M2 source) were mixed uniformly in a high-speed mixer at a molar ratio of Li:Zr:W=8:0:9:0:1, and sintered at 900°C for 10 h in an air atmosphere to obtain Li8Zr 0.9 W 0.1 The core of O6.
[0093] (2) Weighing zirconium propoxide (M source) and the aforementioned core at a molar ratio of Zr:W=1:10, mixing to obtain a first mixture, weighing the first mixture and glucose (carbon source) at a mass ratio of 99:1 to obtain a second mixture, adding the second mixture into pure water at a solid content of 50% to obtain a mixture, sand milling the mixture at a speed of 2500 rpm for 1 h in a sand mill, and drying the obtained mixed slurry in a spray dryer to obtain a powder, sintering the powder at 800°C in a nitrogen atmosphere, and finally obtaining a coating layer containing Li2ZrO3 and carbon material, and a core of Li8Zr 0.9 W 0.1 O6 lithium supplement.
[0094] Examples 2-16 and Comparative Examples 1-6 are consistent with Example 1, and the differences are shown in Table 1, wherein in Comparative Example 3, no M2 source is added when the inner core is formed, in Comparative Example 4, no M1 source is added when the inner core is formed, in Comparative Example 5, no M source is added when the coating layer is formed, and in Comparative Example 6, no carbon source is added when the coating layer is formed.
[0095] Table 1
[0096]
[0097]
[0098] The parameters of the lithium supplement agents in the above examples and comparative examples are shown in Table 2:
[0099] Table 2
[0100]
[0101] The lithium supplement agents in the above examples and comparative examples are prepared into button batteries, and the preparation method is as follows:
[0102] The lithium supplement material, the conductive agent acetylene black, and the adhesive polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, coated on aluminum foil and dried, and stamped with a pressure of 100MPa to form a pole piece with a diameter of 12mm and a thickness of 120μm as the positive pole piece. A lithium metal sheet with a diameter of 17mm and a thickness of 1mm was used as the negative pole piece; a Celgard 2400 porous membrane with a thickness of 25μm was used as the diaphragm; and 1mol / L LiPF6 was used as the electrolyte, in which the solvent was an equal volume mixture of ethylene carbonate (EC) and diethyl carbonate (DEC). The positive pole piece, diaphragm, negative pole piece and electrolyte were assembled into a 2025 button battery in an argon glove box with a water content and an oxygen content of less than 5ppm.
[0103] The button cells in the above-mentioned embodiments and comparative examples were tested as follows, and the test results are shown in Table 2:
[0104] Decomposition potential and charge and discharge capacity: The assembled button cell is subjected to a 3.0V-4.9V, 0.1C rate test, and the charge specific capacity, discharge specific capacity, and discharge specific energy are read from the test software, where the decomposition potential of the lithium supplement agent = discharge specific energy / discharge specific capacity.
[0105] Lithium ion migration rate of lithium supplement: The assembled button cell is subjected to EIS AC impedance test in an electrochemical workstation, and the lithium ion migration rate of the lithium supplement is obtained from the slope of the straight line segment of the AC impedance graph.
[0106] Table 3
[0107]
[0108]
[0109] The test results show that the coating layer on the surface of the lithium supplement in Examples 1-16 can effectively reduce the increase in the viscosity of the positive electrode slurry caused by the alkalinity of the core surface during the use of the lithium supplement, and the processing performance of the positive electrode slurry is better. The initial charging capacity of the lithium supplement is high, indicating that the lithium ions of the lithium supplement are released more fully during the charging process; the initial discharge capacity of the lithium supplement is low, indicating that less lithium ions are re-embedded in the lithium supplement during the discharge process, which can achieve a better in-situ pre-lithiation effect of the lithium battery.
[0110] Figure 1 This is a scanning electron microscope image of the lithium supplement in Example 1, from which it can be seen that the core surface has a coating layer. Figure 2 It shows that the S1 / S2 of the lithium supplement in Example 1 is 0.03, and the S1 / S2 of the lithium supplement in Comparative Example 5 is 0. Figure 3 This is the charge and discharge curve of the button battery in Example 1.
[0111] In Comparative Example 1, the lithium-containing metal oxide in the tetragonal phase in the coating layer of the lithium supplement agent is too little, which significantly increases the viscosity of the positive electrode slurry; in Comparative Example 2, the lithium-containing metal oxide in the tetragonal phase of the lithium supplement agent is too little, which significantly increases the viscosity of the positive electrode slurry. There are more lithium-containing metal oxides in the tetragonal phase, which makes the viscosity of the positive electrode slurry lower, but at the same time, the lithium supplement capacity of the lithium supplement agent is also significantly reduced. In Comparative Example 3, the core of the lithium supplement agent does not contain the M2 element, which makes the lithium ion transmission speed of the core lower, and the core of the lithium supplement agent in Comparative Example 3 does not contain the M1 element, which makes the lithium supplement capacity of the lithium supplement agent too small; in Comparative Example 5, the lithium-containing metal oxide in the tetragonal phase is not formed in the coating layer of the lithium supplement agent, which significantly increases the viscosity of the positive electrode slurry; in Comparative Example 6, no carbon material is formed in the coating layer of the lithium supplement agent, which makes the lithium supplement capacity of the lithium supplement agent poor.
[0112] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.
[0113] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.
[0114] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium supplement, characterized in that: include: a core, the core satisfying the chemical formula Li x M1 y M2 1-y O6, where 6 ≤ x ≤ 8, 0 < y < 1, M1 is at least one of Zr, Nb, Sb, Bi, Ru, Ta, Sn, Hf, Ir, Pr, Pt, Np, M2 is at least one of W, Ge, Ca, Ce, K, Ta, and the ionic radius of the M2 element is greater than the ionic radius of the M1 element; The coating layer is located at least on a portion of the surface of the core, and the coating layer includes a lithium-containing metal oxide and a carbon material, wherein the lithium-containing metal oxide satisfies the chemical formula Li a M b O c , wherein 1.8≤a≤2, 0.7≤b≤1.1, 2.8≤c≤3, M includes Ti and / or Zr, The peak intensity of the diffraction peak of the lithium supplement to X-rays within a 2θ diffraction angle of 20.1°-20.3° is S1, the peak intensity of the diffraction peak of the lithium supplement to X-rays within a 2θ diffraction angle of 17°-17.3° is S2, and S1 / S2 is 0.02-0.
05. The peak intensity of the diffraction peak is obtained by testing with an automatic X-ray diffractometer, and the test conditions are: working voltage 40 kV, working current 250 mA, continuous scanning, scanning speed 4° / min, step length 0.02°, and scanning angle range 10°-80°.
2. The lithium supplement according to claim 1, characterized in that: The mass fraction of the lithium-containing metal oxide in the lithium supplement agent is 0.01%-0.1%, and / or the mass fraction of the carbon material in the lithium supplement agent is 0.01%-0.5%.
3. The lithium supplement according to claim 1, characterized in that: The unit cell parameters of the kernel satisfy a=b, a≠c, wherein c / a is 2-3.
4. The lithium supplement according to claim 3, characterized in that: a is 0.4nm-0.7nm, and c is 1.4nm-1.6nm.
5. The lithium supplement according to any one of claims 1 to 4, characterized in that: The Dv50 particle size of the core is 1 μm-10 μm, and / or the thickness of the coating layer is 50 nm-500 nm.
6. The lithium supplement according to any one of claims 1 to 4, characterized in that: The core includes Li8Zr 0.9 W 0.1 O6、Li7Nb 0.8 Ta 0.2 O6、Li7Sb 0.9 Ta 0.1 O6、Li7Ru 0.7 W 0.2 Ce 0.1 O6、Li8Sn 0.9 Ca 0.1 O6、Li8Hf 0.7 W 0.2 Ca 0.1 O6、Li8Ir 0.6 W 0.2 Ce 0.2 O6、Li8Pr 0.5 W 0.3 Ca 0.2 O6、Li8Pt 0.7 W 0.2 Ca 0.1 At least one of O6.
7. The lithium supplement according to any one of claims 1 to 4, characterized in that: The graphitization degree of the carbon material is greater than or equal to 60%.
8. A method for preparing the lithium supplement according to any one of claims 1 to 7, characterized in that: include: The lithium source, the M1 source and the M2 source are subjected to a first sintering treatment in an oxygen-containing atmosphere to obtain a core; The core, the M source and the carbon source are subjected to a second sintering treatment under an inactive atmosphere to form a coating layer on at least a portion of the surface of the core to obtain the lithium supplement agent.
9. The method according to claim 8, characterized in that The lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium oxide; and / or, The M1 source includes at least one of an oxide of M1, a chloride of M1, a nitrate of M1, and a hydroxide of M1; and / or, The M2 source includes at least one of an oxide of M2, a chloride of M2, a nitrate of M2, and a hydroxide of M2.
10. The method according to claim 9, characterized in that The temperature of the first sintering treatment is 700° C.-1200° C., and the time of the first sintering treatment is 8 h-24 h.
11. The method according to any one of claims 8 to 10, characterized in that: The M source includes at least one of zirconium propoxide, zirconium oxide, zirconium nitrate, zirconium oxychloride, lithium zirconate, zirconium chloride, titanium oxide, titanium tetrachloride, titanium nitrate, and titanium alkoxide; and / or, The carbon source includes at least one of glucose, starch, sucrose and graphite.
12. The method according to claim 11, characterized in that The temperature of the second sintering treatment is 400° C.-800° C., and the time of the second sintering treatment is 6 h-10 h.
13. The method according to claim 8, characterized in that Also includes: Before the second sintering process, the core, the M source, and the carbon source are mixed in a solvent and dried.
14. The method according to claim 13, characterized in that The solvent comprises at least one of ethanol and isopropanol; and / or, The drying process includes at least one of spray drying, freeze drying and flash drying.
15. A positive electrode slurry, characterized in that: The lithium supplement comprises the lithium supplement described in any one of claims 1 to 7, or the lithium supplement prepared by the method described in any one of claims 8 to 14.
16. The positive electrode slurry according to claim 15, characterized in that: The viscosity of the positive electrode slurry is 1000mPa·s-8000mPa·s.
17. A battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode active material layer at least located on one side of the positive electrode current collector, wherein the positive electrode active material layer is prepared by using the positive electrode slurry according to claim 15 or 16.
Citation Information
Patent Citations
Composite lithium supplementing material as well as preparation method and application thereof
CN116364905A
Positive electrode lithium supplementing agent material and preparation method and application thereof
CN117247051A